"Not in My Backyard" is Not Sustainable. Issue 1 (July 2017) - Carson, Ronald S.
Abstract: "Not in my backyard" (NIMBY) is a euphemism for desiring a particular positive outcome from a system that is remotely located such that it has no local negative effect, or a person who exhibits this characteristic. Everyone wants great mobile phone service, for example, but no one wants to look at a mobile phone tower in their backyard. In this paper "exergy destroyed" is applied as a measure of system sustainability to compare NIMBY vs. more "local" system architectures. We analyze transportation of people, goods, and services and show that such transportation is inherently unsustainable because of the exergy destroyed. We use this to show why NIMBY is less sustainable than more localized architectures. We examine dynamic coupling effects on utility generation for NIMBY vs. more local solar electric power architectures and propose an architecture and power distribution method to reduce system costs. We also show that reducing exergy destruction is an inherently lean practice because it reduces waste. Finally, we propose a measure for aligning costs and benefits among different stakeholders as a means to identify more "just" systems.